Determination of the transition point from electron accumulation to depletion at the surface of InxGa1−xN films. (23rd January 2018) - Sun, Xiaoxiao; Wang, Xinqiang; Liu, Shitao; Wang, Ping; Wang, Ding; Zheng, Xiantong; Sang, Liwen; Sumiya, Masatomo; Ueda, Shigenori; Li, Mo; Zhang, Jian; Ge, Weikun; et al.
Abstract: The variation in band bending as a function of the composition at an In x Ga1− x N surface has been investigated via photoassisted Kelvin probe force microscopy. Distinctly different trends in surface photovoltage are observed for Ga-rich alloys compared with In-rich alloys, which is explained in terms of the direction of surface band bending. With the determination of the Fermi energy level at the surface and in the bulk, the results reveal that for an In x Ga1− x N alloy, the transition from a surface electron accumulation layer for In-rich alloys to a surface electron depletion layer for Ga-rich alloys occurs at x ≈ 0.63.